Serum Biomarkers in Oral Lichen Planus: A Biochemical Perspective: Serum Biomarkers and Disease Severity in Oral Lichen Planus - Zhang, Jiawei; Yang, Jie; Lu, Wei; Zang, Shasha; Tong, Chengbi (Journal of Medical Biochemistry, 2025)
Background: Oral lichen planus (OLP) is a chronic inflammatory disease that affects the mucosal tissues of the oral cavity. Its pathogenesis involves immune dysregulation, angiogenesis, and psychological stress. Identifying reliable biomarkers can enhance diagnosis, monitor disease progression, and guide personalized treatment strategies. This study aimed to investigate five key serum biomarkers in OLP patients, including angiopoietin-2 (Ang-2), vitamin D, IgA, IgG, and cortisol, to explore their associations with disease severity. Methods: This observational, case-control study enrolled 100 OLP patients and 80 healthy controls. The OLP patients were classified into three subtypes: reticular (n = 30), atrophic (n = 35), and erosive (n = 35). Fasting blood samples were collected, and serum levels of Ang-2, vitamin D, IgA, IgG, and cortisol were measured using ELISA, HPLC, immunoturbidimetry, and chemiluminescent immunoassays. Statistical analyses, including t-tests, ANOVA, and Pearson correlation, were performed to assess biomarker levels and their correlations with disease severity. Results: Ang-2, IgA, and IgG levels were significantly elevated in OLP patients, particularly in the erosive subtype (P < 0.001), with positive correlations between these markers and disease severity. Vitamin D and cortisol levels were significantly reduced in OLP patients compared to controls (P < 0.01) and showed negative correlations with disease severity. These findings indicate the role of vascular, immune, metabolic, and stress-related factors in OLP pathogenesis. Conclusion: Ang-2, vitamin D, IgA, IgG, and cortisol are valuable biomarkers for assessing OLP severity and guiding personalized treatment. Monitoring these biomarkers can aid in diagnosing OLP, tracking disease progression, and optimizing therapeutic strategies.